Pathogenicity island cag, vacA and IS605 genotypes in Mexican strains of Helicobacter pylori associated with peptic ulcers - Tabche-Barrera María L; Aguilar-Gutiérrez Germán R; Ponce-; Lazcano-Ponce Eduardo C; Castillo-Rojas Gonzalo; López-Vidal Yolanda; Antonio-Rincón Fernando (BMC, 2011)
Abstract Background Helicobacter pylori is associated with chronic gastritis, peptic ulcers, and gastric cancer. Two major virulence factors of H. pylori have been described: the pathogenicity island cag (cag PAI) and the vacuolating cytotoxin gene (vacA). Virtually all strains have a copy of vacA, but its genotype varies. The cag PAI is a region of 32 genes in which the insertion of IS605 elements in its middle region has been associated with partial or total deletions of it that have generated strains with varying virulence. Accordingly, the aim of this work was to determine the cag PAI integrity, vacA genotype and IS605 status in groups of isolates from Mexican patients with non-peptic ulcers (NPU), non-bleeding peptic ulcers (NBPU), and bleeding peptic ulcers (BPU). Methods The cag PAI integrity was performed by detection of eleven targeted genes along this locus using dot blot hybridization and PCR assays. The vacA allelic, cag PAI genotype 1 and IS605 status were determined by PCR analysis. Results Groups of 16-17 isolates (n = 50) from two patients with NPU, NBPU, and BPU, respectively, were studied. 90% (45/50) of the isolates harbored a complete cag PAI. Three BPU isolates lacked the cag PAI, and two of the NBPU had an incomplete cag PAI: the first isolate was negative for three of its genes, including deletion of the cagA gene, whereas the second did not have the cagM gene. Most of the strains (76%) had the vacA s1b/m1 genotype; meanwhile the IS605 was not present within the cag PAI of any strain but was detected elsewhere in the genome of 8% (4/50). Conclusion The patients had highly virulent strains since the most of them possessed a complete cag PAI and had a vacA s1b/m1 genotype. All the isolates presented the cag PAI without any IS605 insertion (genotype 1). Combined vacA genotypes showed that 1 NPU, 2 NBPU, and 1 BPU patients (66.6%) had a mixed infection; coexistence of H. pylori strains with different cag PAI status was observed in 1 NBPU and 2 BPU (50%) of the patients, but only two of these patients (NBPU and BPU) had different vacA genotypes.